The International Legal Framework of Forced Displacement - Shimaa Ibrahim Mohammed Al-Zain; Sarah Balto (International Journal of Law Research and Studies, 2026)
This research examines the international legal framework of forced displacement as one of the most serious violations affecting human dignity, stability, and the right of individuals to remain in their original homeland. It explores the development of this concept from its linguistic and historical meaning to its legal characterization under the rules of international humanitarian law and international criminal law. The study addresses the nature of forced displacement in terms of its linguistic and terminological definition, its roots in ancient civilizations, and the position of Islamic law toward it, before tracing its evolution during the codification of international humanitarian law. It also clarifies the treaty-based and judicial foundations for the criminalization of forced displacement and analyzes its various legal forms as a crime against humanity, a war crime, and, in certain cases, an act that may amount to genocide when accompanied by the intent to destroy, in whole or in part, a protected group. The research concludes that the international prohibition of forced displacement is no longer merely a moral principle or a general humanitarian norm, but has become a binding legal rule that gives rise to international accountability. Nevertheless, the effectiveness of this protection continues to face challenges related to enforcement, evidentiary issues, and selectivity in prosecution. Accordingly, the study emphasizes the importance of strengthening international accountability mechanisms and developing preventive protection measures for civilians in order to limit this crime and safeguard the fundamental rights of civilian populations.